Kinetics of HIV-1 in cerebrospinal fluid and plasma in cryptococcal meningitis - Jorge A. Benetucci; María B. Bouzas; Alicia Arechavala; Diego M. Cecchini; Haroldo Rojas; Ana M. Cañizal; Ricardo Negroni (MDPI AG, 2012)
In order to determine HIV-1 kinetics in cerebrospinal fluid (CSF) and plasma in patients with cryptococcal meningitis (CM), we undertook a prospective collection of paired CSF/plasma samples from antiretroviral therapy- free HIV-infected patients with CM. Samples were obtained at baseline (S1) and at the second (S2) and third (S3) weeks of antifungal therapy. HIV-1 CSF concentrations were significantly lower in both S2 and S3 with respect to S1. Plasma concentrations remained stable. HIV-1 concentrations were higher in plasma than CSF in all cases. Patients who survived the episode of CM (but not those who died) showed a decrease in CSF viral load, what suggests different viral kinetics of HIV-1 in the CSF according to the clinical course of this opportunistic disease.